Weight stigma in Latin America, Asia, Middle East, and Africa: A scoping review - Laura Ann Eggerichs; Oliver W. A. Wilson; John E. Chaplin; Ximena Ramos Salas (Obesity Facts, 2024)
Background: Being stigmatized because of one’s weight can pose physical, mental, and social challenges. While weight stigma and its consequences are established throughout Europe, North America, and Australasia, less is known about weight stigma in other regions. Summary: The objective of this study was to identify the extent and focus of weight stigma research in Latin America, Asia, the Middle East, and Africa. A scoping review of weight stigma research in Latin America, Asia, the Middle East, and Africa was conducted. Results indicate that weight stigma has been investigated across populations and settings, mainly focusing on manifestations of weight stigma through experiences and practices and the drivers, and personal outcomes of these manifestations. Key Messages: Weight stigma is a developing global health concern not restricted to Europe, North America, and Australasia. The extent and focus of weight stigma research in Latin America, Asia, the Middle East, and Africa vary between countries and regions leaving several research gaps that require further investigation.